Flowers supply chain in Paraná Coast - Brazil: an application of Miles and Snow taxonomy - Anacleto, Adilson (Revista Capital Científico - Eletrônica (RCCҽ) - ISSN 2177-4153, 2016)
Paraná Coast had already been a great producer and commercial center of flowers, however in the last decade the supply chain had reduced its cultivation area and marketing. In order to support a better understanding of the strategic management current situation of the flowers production chain in several Brazilian regions based on the similarity found in Paraná Coast, it is presented the results of a research that sought to identify the processes of production, distribution and trade in the flowers supply chain in Paraná Coast, and provide a strategic classification using the Miles and Snow model. It was conducted a descriptive exploratory survey between May 2014 to April 2015, with face interviews to nine farmers, five wholesalers and fifteen retailers. The producers had a defensive strategic posture, the wholesalers showed an analytical strategic posture and the retailers had a reactive strategic posture, and they were the strongest segment of the supply chain due to the organizational skills. In these three levels predominated the commercial rivalry among the segments. It was concluded that the flowers supply chain in Paraná Coast, urgently needs a governance model among the segments that allows performing cooperative practices and harmonic business combination to generate greater competitiveness for the sector.